Constitutional Rights Guarantee and Integrated Licensing System for Sustainable Environmental Development in East Kalimantan - Dani Berlan Ramadhan; Shaffira Maharannie Putri Arkian Arief (Constitutionale, 2023)
Sustainable development in East Kalimantan requires guarantees of constitutional rights and an integrated environmental licensing system. This is important because development that does not pay attention to environmental aspects can have a negative impact on people's quality of life and environmental sustainability. The guarantee of constitutional rights is the first step in protecting people's rights to a healthy and sustainable environment. Meanwhile, an integrated licensing system can minimize adverse environmental impacts and increase compliance and transparency in decision-making. This study examines the importance of guaranteeing constitutional rights and an integrated licensing system in sustainable environmental development in East Kalimantan. The approach used is qualitative by using secondary data such as statutory documents and research reports. The research results show that constitutional rights guarantees and an integrated licensing system are essential in ensuring sustainable development in East Kalimantan. Guaranteed constitutional rights can provide legal certainty and protection of people's rights to a healthy and sustainable environment. Meanwhile, an integrated licensing system can help maintain environmental sustainability and provide legal certainty for investments in sectors that have an impact on the environment. However, there are still challenges in implementing constitutional rights guarantees and integrated licensing systems, such as coordination between agencies, limited human and technological resources, and public awareness about the importance of protecting the environment. Therefore, good coordination between the government, the community and the private sector is needed to protect the environment and ensure sustainable development in East Kalimantan.